1997
DOI: 10.1007/bf02899924
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell hepatitis in adults

Abstract: Giant cell hepatitis is a frequent reaction of the liver to different injuries in newborns and in childhood, but rare in adults. This form of hepatitis is often accompanied by cholestasis and shows fast progression to cirrhosis. In most cases autoimmune, metabolic, toxic or viral origin can be found, but sometimes the etiology remains hidden. This paper introduces two adult giant cell hepatitis cases. Hepatitis C virus infection was the possible origin in the first case and autoimmune disease in the other one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…These drugs presumed to injure the hepatocytes and cause degenerating effect and formation of giant hepatocytes in certain individuals [1, 3, 59]. Most of the reported cases in the literature presented as mild hepatitis [1, 3, 5, 6] except in three; one died due to clometacine induced liver failure [7]; one was a known case of autoimmune hepatitis and was treated with amoxicillin + clavulanate for cellulitis of thigh and clinically deteriorated and required liver transplant [8]. Another case was treated with doxycycline for one week for bacterial bronchitis, and soon he developed acute liver failure and required liver transplant [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These drugs presumed to injure the hepatocytes and cause degenerating effect and formation of giant hepatocytes in certain individuals [1, 3, 59]. Most of the reported cases in the literature presented as mild hepatitis [1, 3, 5, 6] except in three; one died due to clometacine induced liver failure [7]; one was a known case of autoimmune hepatitis and was treated with amoxicillin + clavulanate for cellulitis of thigh and clinically deteriorated and required liver transplant [8]. Another case was treated with doxycycline for one week for bacterial bronchitis, and soon he developed acute liver failure and required liver transplant [9].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in cases of autoimmune hepatitis (AIH), systemic lupus erythematosus, autoimmune hemolytic anemia rheumatoid arthritis, primary sclerosing cholangitis, polyarthritis, ulcerative colitis, polyarteritis nodosa, and primary biliary cirrhosis [1, 2, 5, 7, 1023, 44]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of other possible causes, medicolegal investigators concluded on the basis of autopsy and histological findings that the subdural hemorrhage was the result of a coagulopathy induced by fulminant neonatal giant cell hepatitis. Neonatal giant cell hepatitis is a frequent, but nonspecific, reaction of the liver to various injuries in neonates and during infancy, but rarely develops in adults [11]. This form of hepatitis is often accompanied by cholestasis and is characterized by an unpredictable progression that shows markedly different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Multinucleated fibroblasts were recently discovered in vitro to form as either syncytia or coenocytes, depending on whether the culture contained cell lines or primary fibroblasts, respectively [168]. Multinucleated hepatocytes are found in neonatal giant cell hepatitis and autoimmune hepatitis [169,170]. Multinucleated melanocytes found in nevi and melanomas are described as having a balloon appearance due to large vacuoles or a starburst appearance due to nuclear arrangement in lentigo maligna [171,172].…”
Section: Multinucleated Giant Cellsmentioning
confidence: 98%